PROTECTIVE EFFECTS OF BLUE GREEN ALGAE SPIRULINA FUSIFORMIS AGAINST GALACTOSAMINE-INDUCED HEPATOTOXICITY IN MICE - VEDI, MAHIMA; Kalaiselvan, Sowmiya; Rasool, Mahaboobkhan; PRINCE SABINA, EVAN (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Objective:The present investigation was carried out to assess the protective properties of Spirulina fusiformis against galactosamine induced toxicity in swiss albino mice. Methods:Evaluation of serum glutamate oxaloacetate transferase (SGOT), serum glutamate pyruvate transferase (SGPT), alkaline phosphatase (ALP), serum bilirubin (SBLN), antioxidant status and TNF-α was done and was compared with the standard reference drug silymarin. Results: Galactosamine injection significantly increased the levels of SGOT, SGPT, SBLN and TNF–α in the serum and caused depletion in the antioxidant status in the liver. Administration of Spirulina fusiformis altered these parameters and brought them to normal levels in the control and experimental mice. Conclusion:Hence results of this study clearly indicate that Spirulina fusiformis has hepatoprotective activity against galactosamine induced toxicity in mice. Keywords: Spirulina, antioxidant, galactosamine, hepatoprotective, silymarin